The Relationship Between Market Culture, Clan Culture, Benevolent Leadership, Work Engagement, and Job Performance: Leader’s Dark Triad as a Moderator - Lee, Michelle Chin Chin; Ding, Alyssa Y L * (Sage, 2022)
Benevolent leadership is one of the leadership styles which provides a positive influence on employees. However, the current leadership literature has yet to investigate how benevolent leadership leads to job performance, the processes involved, the relationship between organizational culture and benevolent leadership, and the role of dark side of leaders in affecting this relationship. Using the leader-culture fit framework within an Eastern context, the current study first investigates the relationship between benevolent leadership and job performance through work engagement. The study then compares two contrasting organizational culture (i.e., market culture and clan culture) on benevolent leadership. Finally, the study investigates how leaders' dark triad affects the relationship between organizational culture and benevolent leadership. 374 full-time white-collar employees (Males = 54.01%; Mean age: 32.7 years) from various private organizations within the service industry participated in this study. The results showed that work engagement mediated benevolent leadership and job performance. Market culture showed a negative relationship with benevolent leadership while clan culture showed a positive relationship with benevolent leadership. Benevolent leadership mediated clan culture (but not market culture) and work engagement. Under a high market culture with a high dark triad leader, benevolent leadership is at its lowest level. Under a high clan culture with a low dark triad leader, benevolent leadership is at its highest level. The findings suggest the importance of benevolent leadership within a clan culture (rather than market culture), in aligning with the leader-culture fit framework in increasing employees' work engagement and job performance.